2015
DOI: 10.1002/bdd.1933
|View full text |Cite
|
Sign up to set email alerts
|

Screening of non‐steroidal anti‐inflammatory drugs for inhibitory effects on the activities of six UDP‐glucuronosyltransferases (UGT1A1, 1A3, 1A4, 1A6, 1A9 and 2B7) using LC‐MS/MS

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) are used widely to relieve pain and to decrease inflammation. Several clinical studies have reported that NSAIDs inhibit uridine 5'-diphospho-glucuronosyltransferase (UGT) enzymes. Therefore, the study evaluated the inhibitory potential of 15 NSAIDs on the activities of six UGT isoforms (i.e. UGT1A1, 1A3, 1A4, 1A6, 1A9 and 2B7) in human liver microsomes (HLMs). Among the 15 NSAIDs tested here, mefenamic acid and diclofenac inhibited all UGTs tested in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…However, it showed a lower detection signal than testosterone in the proposed LC‐MS/MS method. The cocktail incubation technique has been used in order to screen simultaneously the activities of several enzymes such as multiple cytochrome P450s or uridine diphosphate glucuronosyltransferases (UGTs) . It is important to optimize substrate concentrations in substrate cocktail incubations to minimize interactions between substrates.…”
Section: Resultsmentioning
confidence: 99%
“…However, it showed a lower detection signal than testosterone in the proposed LC‐MS/MS method. The cocktail incubation technique has been used in order to screen simultaneously the activities of several enzymes such as multiple cytochrome P450s or uridine diphosphate glucuronosyltransferases (UGTs) . It is important to optimize substrate concentrations in substrate cocktail incubations to minimize interactions between substrates.…”
Section: Resultsmentioning
confidence: 99%
“…An in vitro study on human liver microsomes suggested that certain nonsteroidal anti-inflammatory drugs may have an inhibitory potential on UDP-GT isoforms, suggesting that certain mediators of the cyclooxygenase-dependent pathway may be involved in the regulation of DMET activity. However, the underlying mechanism and the clinical relevance in terms of UDP-GT substrate clearance need to be further investigated ( Joo et al, 2015 ).…”
Section: Regulation Of Dmets By Inflammationmentioning
confidence: 99%
“…The use of single doses may be perceived as a limitation. However, neither bazedoxifene nor ibuprofen has been implicated in the induction or inhibition of UGT or CYP2C9; both have multiple‐dose pharmacokinetics that are well predicted by single‐dose observations, and both can be assayed easily after single doses, permitting clear assessment of changes in pharmacokinetics. The results of this study would be expected to predict what would occur after multiple doses and further represent the more common clinical condition, at least for ibuprofen, which is commonly taken as a single dose for treatment of acute pain.…”
Section: Discussionmentioning
confidence: 99%